THE IMPORTANCE OF THE LAWS OF EDUCATION AND TRAINING IN THE SKINS OF PHYSICAL CULTURE - Muminov Sherzod Ilyosovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article analyzes in detail the conditions created by our state and government in the field of physical education and sports, as well as the sports activities organized in educational institutions through the means of physical education and opinions on its importance. To obtain information about the role of physical education tools in human health, this article serves as one of the main sources.